Validation of Immunohistochemistry for Canine Proteins Involved in Thyroid Iodine Uptake and Their Expression in Canine Follicular Cell Thyroid Carcinomas (FTCs) and FTC-Derived Organoids - Jankovic, Jana; Dettwiler, Martina; Fernández, Martin González; Tièche, Eve; Hahn, Kerstin; April-Monn, Simon; Dettmer, Matthias S; Kessler, Martin; Rottenberg, Sven; Campos, Miguel (Veterinary pathology, 2021)
Thyrotropin receptor (TSHR), sodium iodide symporter (NIS), pendrin, and thyroid peroxidase (TPO) are essential for the uptake of iodine by follicular thyroid cells. The aim of this study was to establish immunohistochemistry (IHC) protocols for TSHR, NIS, pendrin, and TPO in canine tissues and characterize their expression in organoids derived from canine follicular cell thyroid carcinoma (FTC) and in the respective primary tumors. This constitutes a fundamental step to establish organoids as a model to study the uptake of iodine in canine FTC. Commercially available antibodies directed against human proteins were selected. Antibody specificity was confirmed by western blot using lysates of the HTori-3 human thyroid cell line and healthy canine thyroid gland. IHC was validated using HTori-3 cells and a set of canine normal tissues including healthy thyroid gland. The expression of TSHR, NIS, pendrin, and TPO was evaluated in 3 organoid lines derived from FTC and respective primary tumors. All 4 antibodies produced specific bands by western blot and cytoplasmic labeling in follicular cells by IHC in both human HTori-3 cells and canine thyroid gland. NIS also showed basolateral membrane immunolabeling in follicular cells. All 4 proteins were highly expressed in organoids derived from FTC. The expression was similar or higher compared to the primary tumors. The results of this study characterize organoids derived from canine FTC as a suitable in vitro model to investigate iodine uptake, opening new research possibilities in the field of canine thyroid cancer therapy.